The Influence of Organizational Culture and Human Resource Quality on Employee Performance with Work Motivation as a Mediating Variable - Fitriani Akib; A. Nur Insan; Muliyadi Hamid (Journal of Management and Administration Provision, 2026)
This research aims to examine how the organizational culture and quality of human resources impact on the employee performance and the connection between work motivation and the work performance. The study was carried out at the Office of the Airport Authority Region V Makassar using quantitative research design. The sampling method was the Slovin formula that resulted in a sample of 116 State Civil Apparatus employees. The methods used included the collection of data through distributed questionnaires and the analysis of the data with the help of the Partial Least Squares (PLS) model which was conducted with the help of SmartPLS 3.0 software. The empirical findings suggest that organizational culture directly and statistically significantly influences the performance of employees. Likewise, quality of the human resource has a direct effect of high influence on employee performance. Moreover, organizational culture and the quality of human resource were identified to have a strong impact on work motivation of employees. Nevertheless, work motivation did not have a statistically significant impact on employee performance implying that it was not effective as a mediating construct. That is, work motivation is influenced by organizational culture and the quality of human resource, but this does not mediate the impact of these antecedents on employee performance. This result suggests that performance enhancement is more mightily defined by the inner organizational quality and competence of the employees than it is by motivation.